Jaringan Sensor Nirkabel: Studi dan Evaluasi Kinerja LoRa Transmitter dan Long Range Radio Frekuensi (RF) Pada Luar Ruang - Rifki Muhendra; Naufal Ismail Kreshnaviyanto; Aisyah Amin (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Transmitters are the backbone of communication on wireless sensor networks. Most transmitters use ism band frequencies so the communication range is limited to 100 m. Some types of transmitters that have long-distance communication capabilities are nRF24 1 km and LoRa. The paper reports a comparative study between nRF24 1 km and LoRa in data communication, power consumption and resistance to obstacles. The results showed that LoRa has a range capability of 1.6 km and nRF24 has a delivery capability of 1 km. The 1 km NRF24 is more suitable for long-distance communication that requires high speed and is also resistant to non-line of sight obstacles.